Evolutive analysis of the Western economic and political domination's strategies in West Africa : from colonization to today - (:unkn) unknown (My University, 2019)
Western imperialism in West Africa, which was primarily European from the late nineteenth century until the late 1950s, was forced to evolve over time, each once a colonial crisis has occurred. Towards the end of the nineteenth century, in Western Europe, the promotion and implementation of doctrines promoting the economic and geopolitical advantages, as well as the humanitarian virtues lent to colonial expansion, will lead to the conquest and colonization of Western Africa traditionals sovereigntys, by the two leading conquering European nations of the time: France and Great Britain. The analysis of the European colonial expansion motivations, as well as the description over time of the systems of political domination and economic exploitation of Europe's "African empires" will be at the basis of the classical and new theories of imperialism. From this period, Western imperialism in West Africa, which was primarily European from the late nineteenth century until the late 1950s, was forced to evolve over time, each once a colonial crisis has occurred. In the specific case of West Africa, the confrontation of the theories of imperialism with the progressive historical and regressive analysis of Afro-Western relations since the first colonial conquests, has revealed to us that Western imperialism was manifested over four main chronological phases. Thus, the first phase of European imperialism in West Africa, which consecrates the all-powerful colonial administration and its economic agents, begins with the colonial conquests, through the processes of horogenesis and ends with the first colonial crisis at the end of the second world war, under the impetus of African nationalisms, sporadic popular socio-political demands arising, then under international pressure. In order to repel these centrifugal factors, the second phase of Western imperialism, which is still European, has made it more necessary for metropolises to grant socio-economic and political in
Keywords: African Research